Screening for obstructive sleep apnoea in an early psychosis cohort: a pilot study. (April 2020) - Lane, Abigail R; Myles, Hannah; Foley, Sharon; Siskind, Dan
Objective: Rates of obstructive sleep apnoea (OSA) appear to be lower in the youth population (< 4%) compared to the general population (6%–17%); rates in people with psychotic illness are estimated at 13.5%–57.1%. We hypothesised that this comorbidity extends to early psychosis (EP) populations, and used previously validated OSA questionnaires to screen for OSA in an EP cohort. Method: Fifty-three patients were screened using the OSA50 and STOP-Bang questionnaires with collection of anthropometric measures. Patients who screened positively were referred for polysomnography. Results: Fifteen per cent (8/53) screened positively; most frequently endorsed measures included BMI > 25, snoring, hypertension, neck circumference (> 40 cm) and male gender. Only 2/8 patients accepted polysomnography. Conclusions: Screening indicates OSA may be more prevalent in EP populations than age-equivalent cohorts, but ongoing research is required.